A polylactic acid material with silky effect based on FDM and preparation method thereof
By adding modified polylactic acid and modified filler to polylactic acid materials, the toughness and heat resistance of the material are improved, the brittleness and compatibility problems of polylactic acid materials in 3D printing are solved, and the silky effect is achieved. in FDM technology.
Patent Information
- Application Number
- CN202410606152.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-16
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-05-16
AI Technical Summary
As a 3D printing material, polylactic acid has problems such as high brittleness, insufficient printing, and insufficient silky surface. The existing technology has poor compatibility after adding TPU as an additive, resulting in a degradation of performance and limiting its application.
A preparation method based on FDM is adopted to form a prepolymer by reaction of lactic acid, trichrysol isooctanoate, and p-toluenesulfonic acid monohydrate, and ethylene glycol bis(4-carboxyphenyl) ether, The TPU performs reduced compression polycondensation, combined with hydrophobic lignin and modified fillers, and prepares a modified polylactic acid composition to improve toughness, mechanical properties and heat resistance, while achieving silky effect.
The prepared polylactic acid material has good fluidity, improved heat resistance and toughness, and has silky effect. It is suitable for FDM technology, which solves the brittleness and compatibility problems of polylactic acid material in 3D printing and improves its 3D printing. performance in.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of polylactic acid materials, and specifically discloses a polylactic acid material with a silky effect based on FDM and a preparation method thereof. Background Art
[0002] FDM technology is a 3D printing technology that uses thermoplastics as consumables. 3D printing technology is also known as additive manufacturing. Commonly used raw materials include polylactic acid, acrylonitrile-butadiene-styrene terpolymer, polyethylene terephthalate-1,4-cyclohexanedimethanol, etc.
[0003] Among them, polylactic acid has good processability and is degradable, and is a hot topic of research; however, when polylactic acid is used as a 3D printing raw material, it has problems such as high brittleness, insufficient printing smoothness, and an unsmooth surface. The existing technology adds TPU (thermoplastic polyurethane elastomer rubber) particles as an additive to toughen polylactic acid and make it have a silky effect, but there are still problems such as performance degradation due to poor compatibility, which limits its application; therefore, it is of great significance to study a polylactic acid material and preparation method with good toughness, good mechanical properties, good heat resistance, good processability and a silky effect. Summary of the invention
[0004] The object of the present invention is to provide a polylactic acid material with a silky effect based on FDM and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a polylactic acid material with a silky effect based on FDM, comprising the following steps: S1: taking lactic acid, trimesic acid, stannous isooctanoate, and p-toluenesulfonic acid monohydrate, and reacting to form a prepolymer; heating the prepolymer, adding ethylene glycol bis(4-carboxyphenyl) ether and TPU (thermoplastic polyurethane elastomer rubber), and performing compression polymerization to obtain a modified polylactic acid A;
[0006] S2: Take polylactic acid, hydrophobized lignin, stannous isooctanoate, and p-toluenesulfonic acid monohydrate, raise the temperature and stir to obtain modified polylactic acid B;
[0007] S3: polylactic acid, modified polylactic acid A and modified polylactic acid B are mixed to obtain a polylactic acid composition; polybutylene adipate, TPU, polylactic acid composition, modified filler and antioxidant are mixed evenly, melt-blended and extruded to obtain polylactic acid material.
[0008] More optimally, the preparation of the prepolymer includes the following steps: take lactic acid, trimesic acid, stannous isooctanoate, and p-toluenesulfonic acid monohydrate, heat them at 105-110°C under reduced pressure for 0.5-1h, raise the temperature to 130-135°C and heat for 0.5-1h to obtain a prepolymer.
[0009] More optimally, the time for the reduced pressure polymerization is 20 to 24 hours.
[0010] More optimally, it is characterized in that the modified polylactic acid A comprises the following raw materials, calculated by mass: 25-35 parts of lactic acid, 3-6 parts of trimesic acid, 0.1-0.15 parts of stannous isooctanoate, 0.02-0.05 parts of p-toluenesulfonic acid monohydrate, 2-5 parts of ethylene glycol bis(4-carboxyphenyl) ether, and 2-5 parts of TPU.
[0011] More optimally, it is characterized in that: the modified polylactic acid B comprises the following raw materials, calculated by mass: 30-40 parts of polylactic acid, 3-4 parts of hydrophobized lignin, 0.1-0.15 parts of stannous isooctanoate, and 0.02-0.05 parts of p-toluenesulfonic acid monohydrate.
[0012] More optimally, in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is (1~2):1:1.
[0013] More optimally, the polylactic acid material includes the following raw materials, calculated by weight: 8 to 15 parts of polybutylene adipate, 5 to 10 parts of TPU, 100 parts of polylactic acid composition, 20 to 25 parts of modified filler, and 0.1 to 0.5 parts of antioxidant.
[0014] More optimally, the preparation of the modified filler includes the following steps: taking dibenzoyl peroxide, methyl methacrylate, and 4-vinylbenzyl glycidyl ether, heating, adding a carbon-based material, stirring, filtering, and drying to obtain a modified filler.
[0015] More optimally, the modified filler includes the following raw materials: 0.05-0.08 parts of dibenzoyl peroxide, 40-50 parts of methyl methacrylate, 8-15 parts of 4-vinylbenzyl glycidyl ether, and 15-25 parts of carbon-based materials; the carbon-based materials include one or more of carbon nanotubes, graphene, and silicon carbide.
[0016] Preferably, the carbon-based material is carbon nanotube.
[0017] More optimally, the preparation of the hydrophobized lignin includes the following steps: taking lignin and pyridine, stirring and dissolving them, adding acetic anhydride, stirring to obtain a mixture, dropping the mixture into cold water to precipitate it, filtering, washing, and drying to obtain the hydrophobized lignin.
[0018] More optimally, the hydrophobized lignin comprises the following raw materials, calculated by weight: 1-2 parts of lignin, 10-15 parts of pyridine, and 1-2 parts of acetic anhydride.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a polylactic acid material is prepared by using polybutylene adipate, TPU, a polylactic acid composition and a modified filler; polylactic acid has good fluidity and can be naturally degraded, but when used as a 3D printing material, it has the defects of insufficient heat resistance and poor toughness; polybutylene adipate has good compatibility with polylactic acid, and adding polybutylene adipate to blend can improve the toughness of polylactic acid, but the tensile strength is slightly reduced and the thermal conductivity is not greatly improved; therefore, TPU is introduced to improve the heat resistance and tensile strength of polylactic acid, and at the same time make the polylactic acid have a silky effect;
[0020] In order to solve the problem of poor compatibility between TPU and polylactic acid and polybutylene adipate and further improve the toughness, mechanical properties and heat resistance of polylactic acid materials, a polylactic acid composition including polylactic acid, modified polylactic acid A and modified polylactic acid B is prepared;
[0021] Modified polylactic acid B is prepared from polylactic acid and hydrophobic lignin. Lignin has good strength and can improve the brittleness of polylactic acid. However, due to the presence of a large number of hydroxyl groups on the surface, it has poor compatibility with polylactic acid. Therefore, acetylated hydrophobic lignin is prepared and compounded with polylactic acid to obtain modified polylactic acid B with high strength. However, due to the introduction of lignin, the viscosity of modified polylactic acid B increases and the processability deteriorates. Therefore, modified polylactic acid A is introduced.
[0022] The modified polylactic acid A is first prepared with lactic acid and trimesic acid to prepare a prepolymer. Due to the addition of trimesic acid, the prepolymer has a multi-branched structure and has good toughness and fluidity. Then, ethylene glycol bis(4-carboxyphenyl) ether and TPU are added to perform reduced pressure polymerization. Ethylene glycol bis(4-carboxyphenyl) ether has good flexibility, which can improve toughness and processing performance. Here, TPU is introduced into the modified polylactic acid A, which not only increases the heat resistance and strength of the modified polylactic acid A, but also improves the compatibility between the polylactic acid and the TPU added in the subsequent steps, thereby enhancing the performance and silky effect of the polylactic acid material.
[0023] The polylactic acid composition is added with polylactic acid, modified polylactic acid A and modified polylactic acid B in a certain proportion, which has good toughness, mechanical strength, heat resistance and processability, and has good compatibility with TPU and polybutylene adipate added in the subsequent steps, and has a good silky effect when used for 3D printing;
[0024] In order to improve the dispersibility of the inorganic filler, dibenzoyl peroxide, methyl methacrylate and 4-vinylbenzyl glycidyl ether are used to modify it to prepare a modified filler; the modified filler is coated with a layer of polymethyl methacrylate, which has good compatibility with polylactic acid and plays a reinforcing role, and is helpful to improve the heat resistance and mechanical properties. At the same time, the surface of the modified filler contains a large number of epoxy groups, which can increase the degree of crosslinking and the compatibility between the components of the polylactic acid composition, and further improve the performance of the polylactic acid composition. DETAILED DESCRIPTION
[0025] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0026] The following parts are by mass unless otherwise specified;
[0027] Example 1: S1: Take 30 parts of lactic acid, 4 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat at 110°C under reduced pressure for 0.5h, heat to 135°C and heat for 1h to obtain a prepolymer; heat to 160°C, add 3 parts of ethylene glycol bis(4-carboxyphenyl) ether and 4 parts of TPU, and polymerize under reduced pressure for 24h to obtain modified polylactic acid A;
[0028] S2: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 35 parts of polylactic acid, 4 parts of hydrophobized lignin, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 5 hours to obtain modified polylactic acid B;
[0029] S3: Take 0.06 parts of dibenzoyl peroxide, 42 parts of methyl methacrylate, and 12 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 20 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0030] S4: Take 12 parts of polybutylene adipate, 6 parts of TPU, 100 parts of polylactic acid composition, 22 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 1:1:1.
[0031] Example 2: S1: Take 35 parts of lactic acid, 6 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat at 110°C under reduced pressure for 0.5h, heat to 135°C and heat for 1h to obtain a prepolymer; heat to 160°C, add 5 parts of ethylene glycol bis(4-carboxyphenyl) ether and 5 parts of TPU, and polymerize under reduced pressure for 24h to obtain modified polylactic acid A;
[0032] S2: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 40 parts of polylactic acid, 4 parts of hydrophobized lignin, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 5 hours to obtain modified polylactic acid B;
[0033] S3: Take 0.06 parts of dibenzoyl peroxide, 50 parts of methyl methacrylate, and 15 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 25 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0034] S4: Take 15 parts of polybutylene adipate, 10 parts of TPU, 100 parts of polylactic acid composition, 25 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 1:1:1.
[0035] Example 3: S1: Take 25 parts of lactic acid, 3 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat at 110°C under reduced pressure for 0.5h, heat to 135°C and heat for 1h to obtain a prepolymer; heat to 160°C, add 2 parts of ethylene glycol bis(4-carboxyphenyl) ether and 2 parts of TPU, and polymerize under reduced pressure for 24h to obtain modified polylactic acid A;
[0036] S2: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 30 parts of polylactic acid, 3 parts of hydrophobized lignin, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 5 hours to obtain modified polylactic acid B;
[0037] S3: Take 0.06 parts of dibenzoyl peroxide, 40 parts of methyl methacrylate, and 8 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 15 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0038] S4: Take 8 parts of polybutylene adipate, 5 parts of TPU, 100 parts of polylactic acid composition, 20 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 1:1:1.
[0039] Example 4: S1: Take 25 parts of lactic acid, 6 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.05 parts of p-toluenesulfonic acid monohydrate, heat at 110°C under reduced pressure for 0.5h, heat to 130°C and heat for 1h to obtain a prepolymer; heat to 160°C, add 5 parts of ethylene glycol bis(4-carboxyphenyl) ether and 5 parts of TPU, and polycondense under reduced pressure for 20-24h to obtain modified polylactic acid A;
[0040] S2: Take 2 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 15 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 30 parts of polylactic acid, 4 parts of hydrophobized lignin, 0.15 parts of stannous isooctanoate, and 0.02 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 4 hours to obtain modified polylactic acid B;
[0041] S3: Take 0.08 parts of dibenzoyl peroxide, 40 parts of methyl methacrylate, and 15 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 25 parts of carbon nanotubes, stir at 90°C for 1 hour, filter, and dry to obtain a modified filler;
[0042] S4: Take 15 parts of polybutylene adipate, 10 parts of TPU, 100 parts of polylactic acid composition, 25 parts of modified filler, and 0.1 part of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 200°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 2:1:1.
[0043] Comparative Example 1 (changing the amount of raw materials added in the polylactic acid composition, and the other method steps are consistent with Example 1): S1: Take 30 parts of lactic acid, 4 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat at 110° C. under reduced pressure for 0.5 h, heat to 135° C. and heat for 1 h to obtain a prepolymer; heat to 160° C., add 3 parts of ethylene glycol bis(4-carboxyphenyl) ether and 4 parts of TPU, and perform reduced pressure polymerization for 24 h to obtain modified polylactic acid A;
[0044] S2: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 35 parts of polylactic acid, 4 parts of hydrophobized lignin, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 5 hours to obtain modified polylactic acid B;
[0045] S3: Take 0.06 parts of dibenzoyl peroxide, 42 parts of methyl methacrylate, and 12 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 20 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0046] S4: Take 12 parts of polybutylene adipate, 6 parts of TPU, 100 parts of polylactic acid composition, 22 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 1:0.5:1.5.
[0047] Comparative Example 2 (changing the amount of modified filler added, the remaining method steps are consistent with Example 1): S1: Take 30 parts of lactic acid, 4 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat at 110° C. under reduced pressure for 0.5 h, heat to 135° C. and heat for 1 h to obtain a prepolymer; heat to 160° C., add 3 parts of ethylene glycol bis(4-carboxyphenyl) ether and 4 parts of TPU, and perform reduced pressure polymerization for 24 h to obtain modified polylactic acid A;
[0048] S2: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 35 parts of polylactic acid, 4 parts of hydrophobized lignin, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 5 hours to obtain modified polylactic acid B;
[0049] S3: Take 0.06 parts of dibenzoyl peroxide, 42 parts of methyl methacrylate, and 12 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 20 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0050] S4: Take 12 parts of polybutylene adipate, 6 parts of TPU, 100 parts of polylactic acid composition, 30 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 1:1:1.
[0051] Comparative Example 3 (using double-modified polylactic acid to replace modified polylactic acid A and modified polylactic acid B, and the remaining steps are consistent with Example 1): S1: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously to dissolve at 125°C, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobic lignin;
[0052] S2: Take 60 parts of lactic acid, 4 parts of trimesic acid, 0.15 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat at 110°C under reduced pressure for 0.5h, heat to 135°C and heat for 1h to obtain a prepolymer; heat to 160°C, add 3 parts of ethylene glycol bis(4-carboxyphenyl) ether, 4 parts of TPU, and 4 parts of hydrophobized lignin, and polymerize under reduced pressure for 24h to obtain a double-modified polylactic acid;
[0053] S3: Take 0.06 parts of dibenzoyl peroxide, 42 parts of methyl methacrylate, and 12 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 20 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0054] S4: Take 12 parts of polybutylene adipate, 6 parts of TPU, 100 parts of polylactic acid composition, 22 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid to double-modified polylactic acid is 1:2.
[0055] Comparative Example 4 (the preparation method of modified polylactic acid A is changed, and the remaining steps are consistent with Example 1): S1: Take polylactic acid, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160° C., add 3 parts of ethylene glycol bis(4-carboxyphenyl) ether and 4 parts of TPU, and stir for 6 hours to obtain modified polylactic acid A;
[0056] S2: Take 1.5 parts of lignin and 15 parts of pyridine, stir vigorously at 125°C to dissolve, add 2 parts of acetic anhydride, stir for 14 hours to obtain a mixture, add the mixture dropwise into cold water to precipitate it, filter, wash, and dry to obtain hydrophobized lignin; take 35 parts of polylactic acid, 4 parts of hydrophobized lignin, 0.1 parts of stannous isooctanoate, and 0.03 parts of p-toluenesulfonic acid monohydrate, heat to 160°C and stir for 5 hours to obtain modified polylactic acid B;
[0057] S3: Take 0.06 parts of dibenzoyl peroxide, 42 parts of methyl methacrylate, and 12 parts of 4-vinylbenzyl glycidyl ether, heat to 90°C, keep warm for 5 minutes, add 20 parts of carbon nanotubes, stir at 90°C for 2 hours, filter, and dry to obtain a modified filler;
[0058] S4: Take 12 parts of polybutylene adipate, 6 parts of TPU, 100 parts of polylactic acid composition, 22 parts of modified filler, and 0.2 parts of antioxidant, mix them evenly, melt-blend, extrude and granulate them at 195°C to obtain polylactic acid material; in the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is 1:1:1.
[0059] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: lactic acid (S11077, Shanghai Yuanye); trimesic acid (S48328, Shanghai Yuanye); stannous isooctanoate (S3252, Sigma-Aldrich); p-toluenesulfonic acid monohydrate (CAS: 6192-52-5); ethylene glycol bis(4-carboxyphenyl) ether (CAS: 3753-05-7, Y35524, Shanghai Yuanye); TPU (Bayer 345, Germany); lignin (L552047, Xinxinjia); pyridine (CAS: 110-86-1); acetic anhydride (CAS: 108-24-7); polylactic acid (S30789, Shanghai Yuanye); dibenzoyl peroxide (CAS: 94-36-0); methyl methacrylate (CAS: 80-62-6); 4-vinylbenzyl glycidyl ether (YK6195, Hubei Yongkuo Technology Co., Ltd.); carbon nanotubes (T19281, Shanghai Yuanye); polybutylene adipate (A103871, Zhengzhou Alpha Chemical Co., Ltd.); antioxidant (antioxidant 1010, S67391, Shanghai Yuanye).
[0060] Experiment: The polylactic acid materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were extruded, pulled, and drawn by a single screw extruder. The extrusion temperature was 200°C, the pulling speed was 60 mm / s, and the diameter of the consumables was controlled to be 1.75 mm, respectively, to obtain materials for 3D printing. Referring to GB / T 1040.2-2006, 1B type specimens were prepared by a 3D printer, and the specimens were tested: (1) the tensile strength was tested according to GB / T 1040-2006, and the tensile speed was 5 mm / min; (2) the tensile strength was tested according to A of GB / T 1633-2000. 120 (3) Evaluate its 3D printing performance; see the table below for specific data;
[0061]
[0062] Conclusion: In comparative example 1, the amount of raw materials added in the polylactic acid composition is changed, and the performance decreases. It can be seen that controlling the amount of raw materials added in the polylactic acid composition is of great significance; in comparative example 2, the amount of modified filler added is increased, and the performance becomes worse and there is a slight blockage during printing. It can be seen that the amount of modified filler added needs to be controlled; in comparative example 3, double-modified polylactic acid is used to replace modified polylactic acid A and modified polylactic acid B. Due to the influence of grafting rate and steric hindrance, the performance decreases; in comparative example 4, the preparation method of modified polylactic acid A is changed, and trimesic acid is not added. Polylactic acid is directly obtained by modifying ethylene glycol bis(4-carboxyphenyl) ether and TPU, resulting in structural changes and performance is not as good as the embodiment; in summary, the polylactic acid material prepared by the present invention has good mechanical properties, good toughness, good heat resistance, good printability, and is suitable for FDM technology.
[0063] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a polylactic acid material with a silky effect based on FDM, characterized in that: The method comprises the following steps: S1: taking lactic acid, trimesic acid, stannous isooctanoate and p-toluenesulfonic acid monohydrate, reacting to form a prepolymer; heating the prepolymer, adding ethylene glycol bis(4-carboxyphenyl) ether and thermoplastic polyurethane elastomer rubber, and performing compression polymerization to obtain modified polylactic acid A; S2: Take polylactic acid, hydrophobized lignin, stannous isooctanoate, and p-toluenesulfonic acid monohydrate, raise the temperature and stir to obtain modified polylactic acid B; S3: mixing polylactic acid, modified polylactic acid A and modified polylactic acid B to obtain a polylactic acid composition; taking polybutylene adipate, thermoplastic polyurethane elastomer rubber, polylactic acid composition, modified filler and antioxidant, mixing them evenly, and melt-blending and extruding and granulating them to obtain a polylactic acid material; The modified polylactic acid A comprises the following raw materials, calculated by weight: 25-35 parts of lactic acid, 3-6 parts of trimesic acid, 0.1-0.15 parts of stannous isooctanoate, 0.02-0.05 parts of p-toluenesulfonic acid monohydrate, 2-5 parts of ethylene glycol bis(4-carboxyphenyl) ether, and 2-5 parts of thermoplastic polyurethane elastomer rubber; The modified polylactic acid B comprises the following raw materials, calculated by weight: 30-40 parts of polylactic acid, 3-4 parts of hydrophobized lignin, 0.1-0.15 parts of stannous isooctanoate, and 0.02-0.05 parts of p-toluenesulfonic acid monohydrate; In the polylactic acid composition, the mass ratio of polylactic acid, modified polylactic acid A, and modified polylactic acid B is (1-2):1:1; The polylactic acid material comprises the following raw materials, calculated by weight: 8 to 15 parts of polybutylene adipate, 5 to 10 parts of thermoplastic polyurethane elastomer rubber, 100 parts of polylactic acid composition, 20 to 25 parts of modified filler, and 0.1 to 0.5 parts of antioxidant; The preparation of the modified filler comprises the following steps: taking dibenzoyl peroxide, methyl methacrylate, and 4-vinylbenzyl glycidyl ether, heating, adding a carbon-based material, stirring, filtering, and drying to obtain a modified filler; The modified filler comprises the following raw materials: 0.05-0.08 parts of dibenzoyl peroxide, 40-50 parts of methyl methacrylate, 8-15 parts of 4-vinylbenzyl glycidyl ether, and 15-25 parts of carbon-based materials; the carbon-based materials comprise one or more of carbon nanotubes, graphene, and silicon carbide.
2. The method for preparing a polylactic acid material with a silky effect based on FDM according to claim 1, characterized in that: The preparation of the hydrophobized lignin comprises the following steps: taking lignin and pyridine, stirring and dissolving, adding acetic anhydride, stirring to obtain a mixture, dropping the mixture into cold water to precipitate it, filtering, washing, and drying to obtain the hydrophobized lignin.
3. The method for preparing a polylactic acid material with a silky effect based on FDM according to claim 2, characterized in that: The hydrophobized lignin comprises the following raw materials, calculated by weight: 1 to 2 parts of lignin, 10 to 15 parts of pyridine, and 1 to 2 parts of acetic anhydride.
4. The polylactic acid material prepared according to the method for preparing a polylactic acid material with a silky effect based on FDM according to any one of claims 1 to 3.
